The Strategic Role of Customs Intelligence in Handling Smuggling of Goods in the Strait of Malacca - Amirudin Amirudin; Arthur Josias Simon Runturambi (Budapest International Research and Critics University, 2022)
The Malacca Strait is a waters prone to the smuggling of various goods. The smuggling crosses the borders of Indonesia and Malaysia. Since 1994, the two countries have cooperated in the form of a coordinated patrol (PATKOR KASTIMA) to deal with smuggling in the Malacca Strait. Customs intelligence support is needed by both countries for the optimization of coordinated patrols. This study uses qualitative methods, data collection is carried out by literature studies and interviews with competent resource persons at the Directorate General of Customs and Excise (DGCE) and the Royal Malaysian Customs Department (RMCD). The results show that customs intelligence carried out by Indonesia and Malaysia during coordinated patrols is a tactical intelligence activity that produces strategic intelligence and supports strategic decisions of the two countries at the national, regional and global levels.